Pembelajaran IPA Dalam Meningkatkan Preferensi Makanan Tradisional - Asrorul Azizi; Mulia Rasyidi; Muhammad Sarjan; Agus Muliadi; Hamidi Hamidi; Iswari Fauzi; Muhammad Yamin; Muh. Zaini Hasanul Muttaqin; Bakhtiar Ardiansyah; Rindu Rahmatiah; Sudirman Sudirman; Yusran Khery (Peneliti.net, 2022)
This study is one of the efforts to examine the literature because there is still limited reconstruction of the original science that developed in society into scientific science. This study can then be developed and applied by students as a source of independent learning. The study of local potential in science learning is very important to do, considering that not many have comprehensively analyzed this topic. The local potential that exists in each region can be a wealth of references in learning. Local potential in the form of natural resources, language, customs, arts and can be a wealth of food. Since ancient times, the role of food has been studied as an ingredient to fulfill nutritional needs. Without realizing it, food, especially traditional food, has become the identity of a nation. Traditional food can be a reflection of the geographical, social and cultural conditions that are unique to a nation. This research is important to do so that the potential for research can be known and can be used as a consideration in developing further learning designs. The purpose of this study is to reconstruct the concept of science learning to increase local food preferences into scientific science, as well as to explain science material related to the reconstruction of original science in the process of making traditional food.